(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In the article academic in writing to success directed goals and writing strategies mutual dependency research Research mixture methods ( questionnaire , written affairs analysis , interview ) based on take Go to Uzbekistan supreme education in institutions English language studying in the field of students participation Results this shows that to "mastery goal". has students academic in writing analytical , reflexive and creative strategies active uses this and their writing quality increases . “Performance goal” type students and grammatical correctness and external to evaluate more attention focuses on . Research results academic the record in teaching motivational approach and strategic teaching integration efficiency proves.